University Education and the Value Projection of the Concept of Corporate Social Responsibility - N. D. Tskhadaya; D. N. Bezgodov; О. I. Belyaeva (Высшее образование в России)
The authors consider the concept of corporate social responsibility (CSR) as a component of the global capitalist ideology. The value disposition of universities in relation to the concept of CSR is analyzed relying on the fundamental motivational matrix (FMM). The fundamental types of motivation are defined according to the anthropological distinction between personality and human nature and the social distinction between reward and punishment. In accordance with the logic of the applicability of different types of motivation, the fundamental contradiction between the value basis of the capitalist economy and the main scientific and educational activities of universities is determined. The attitude of voluntary responsibility characteristic of CSR is defined as internally contradictory, but unavoidable within the system of declared values of the capitalist economy. It is shown that the peripheral position of labor in this system of values is not accidental, that labor and investment success are opposed, and that it is irrevocable.